Analisis Kinerja Mesin High Grade Fugal Dengan Metode TPM Melalui Pengukuran OEE di PT. Sinergi Gula Nusantara Tjoekir: Analysis of High Grade Fugal Machine Performance with Total Productive Maintanance (TPM) Method at PT. Sinergi Gula Nusantara Tjoekir - Shofa, Nailis; Muflihah, Nur (INVANTRI (Inovasi Dan Pengelolaan Industri), 2025)
PT Sinergi Gula Nusantara Tjoekir is a company engaged in the management of sugar factories. The level of machine performance is a key factor in maintaining the productivity and operationalefficiency of a factory or manufacturing facility. The problem that occurs on the High Grade Fugal machine is the occurrence of downtime due to lack of stability in engine play (hunting) and so on. This study aims to determine the effectiveness of machine performance, determine the factors that cause losses on the high grade fugal machine and provide suggestions for improvements to reduce losses in order to achieve optimal machine performance.After doing calculations from May to September 2023, the high grade fugal machine has an effectiveness level, namely Overall Equipment Effectiveness is 80.99%, still below the Word Class standard of 85%. While the average Availability value on the machine is 99.88%, the average Performance Rate value is 86.01%, and the average Quality Rate is 94.46%. Indicates a decrease in machine speed so that it can hinder the production process and affect the company's productivity level.